The Effect of Islamic Education Subject on the Development of Student Social Behavior - Diny Kristianty Wardany (BIRCU, 2019)
This research departs from the assumption that learning Islamic Education is expected to be able to develop several obstacles in the lives of students both in the community and schools to students who behave well, learning activities and introduce good behavior to students, aiming to make students obedient in worshiping in the form of Islamic social morality. This research was conducted with quantitative methods, where data was taken through observation, interviews and research questionnaires, which were then processed using product moment techniques, the purpose of which was to find out the relationship between Islamic Education and the development of students' social behavior. The results showed that Islamic Education and students 'social behavior mostly showed good categories, and the results of hypothesis testing showed that learning Islamic Education had a strong relationship with the development of students' social behavior.